THE EFFECT OF BEVACIZUMAB ON ALPHA SMOOTH MUSCLE ACTINEXPRESSION AND FIBROBLAST COUNT TO PREVENT POSTTRABECULECTOMY FIBROSIS IN NEW ZEALAND WHITE RABBIT - Ayu Sitoresmi, Sekar; Nurwasis,; Komaratih, Evelyn; Heriyawatih, (International Journal of Psychosocial Rehabilitation, 2020)
Background: The wound healing process is the most common cause of glaucoma surgery failure that causes the incapability of controlling the intraocular pressure (IOP) and progressive optic nerve damage.Objective: This study aimed to analyze the effect of Bevacizumab on myofibroblast and fibroblast in the trabeculectomy area of rabbit models in order to find a safer wound healing modulator to improve surgical outcomes.Method: Sixteen New Zealand white rabbits aged 4-6 months and weighing between 2.5 and 3.5 kg underwent trabeculectomy on the right eye with a postoperative subconjunctival injection of BSS and Bevacizumab. Subjects were put into a control and bevacizumab groups. Examinations were done, and subjects were terminated and performed enucleation on postoperative day 14. Samples were histologically stained with hematoxyline-eosin to count the fibroblast.Result: Mann Whitney u test and independent t-test were used to analyse the data. We found both less expression of alpha smooth muscle act and a lower fibroblast count in the bevacizumab group compared to the control group, which indicates less myofibroblast, fibroblast, and scarring potential in the trabeculectomy area. There is a significant decrease in expression of α-SMA in the bevacizumab group compared to the control group (p = 0.0195), and with an independent t-test, we found less fibroblast in the bevacizumab group significantly (p = 0.0005).Conclusion: Bevacizumab inhibits fibroblast proliferation and its differentiation to myofibroblast, which leads to less collagen production and fibrosis.